2019
DOI: 10.3389/fimmu.2019.00789
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Neu5Gc and Presence of Anti-Neu5Gc Antibodies in Humans—An Evolutionary Perspective

Abstract: The glycocalyx of human cells differs from that of many other mammals by the lack of the sialic acid N-glycolylneuraminic acid (Neu5Gc) and increased abundance of its precursor N-acetylneuraminic acid (Neu5Ac). Most humans also have circulating antibodies specifically targeting the non-human sialic acid Neu5Gc. Recently, several additional mammalian species have been found to also lack Neu5Gc. In all cases, loss-of-function mutations in the gene encoding the sialic acid-modifying enzyme CMAH are responsible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 72 publications
1
75
0
Order By: Relevance
“…Neu5Ac has an acetyl group on the fifth carbon atom (C5) while Neu5Gc has a glycolyl group instead. Interestingly, humans lack Neu5Gc caused by the mutation of the cytidine monophosphate N-acetylneuraminic acid hydroxylase (CMAH) gene that codes the enzyme transforming CMP-Neu5Ac to CMP-Neu5Gc [3][4][5]. However, Neu5Gc is still found in the human glycome as it can be obtained through dietary sources [6].…”
Section: Introductionmentioning
confidence: 99%
“…Neu5Ac has an acetyl group on the fifth carbon atom (C5) while Neu5Gc has a glycolyl group instead. Interestingly, humans lack Neu5Gc caused by the mutation of the cytidine monophosphate N-acetylneuraminic acid hydroxylase (CMAH) gene that codes the enzyme transforming CMP-Neu5Ac to CMP-Neu5Gc [3][4][5]. However, Neu5Gc is still found in the human glycome as it can be obtained through dietary sources [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its absence in humans, Neu5Gc was found to be absent in some mammalian groups such as New World monkeys, sperm whales, ferrets and white-tailed deer [109]. These observations may suggest that the scenario of catastrophic selection by elimination of Neu5Gc and the ensuing production of natural anti-Neu5Gc antibody, as that in hominins, also occurred in the course of evolution of several mammalian species.…”
Section: Suggested Significance Of Viral Neu5gc Interaction With Antimentioning
confidence: 87%
“…The synthesis of Neu5Gc in many mammalian and primate cells vs. the absence of this antigen and production of natural anti-Neu5Gc antibody in humans raised the possibility that multiple zoonotic viruses replicating in various mammalian reservoirs are likely to present Neu5Gc on their envelope glycans and that anti-Neu5Gc antibody may serve as an immune barrier against infections by such viruses [63,109]. Recent studies indeed demonstrated complement-dependent virolysis of vesicular stomatitis virus (VSV) presenting Neu5Gc (i.e., replicating in African Green monkey Vero cells) by natural anti-Neu5Gc antibody within human serum [63].…”
Section: Distribution Of Neu5gc and Lysis Of Viruses Presenting Itmentioning
confidence: 99%
“…However, the sialic acid family includes several derivatives of the nine-carbon sugar neuraminic acid. In pigs, apes, and Old World nonhuman primates, N-glycolylneuraminic acid (Neu5Gc) is the non-Gal antigen primarily expressed but in humans it is N-acetyneuraminic acid (Neu5Ac) [10]. These innate anti-Neu5Gc antibodies inevitably provoke chronic inflammation that chiefly contribute to the side effects from the use of porcine SIS-ECM [11].…”
Section: Introductionmentioning
confidence: 99%